Analysis of the structure of nanocomposites of triglyceride platelets and DNA1. Issue 27 (21st July 2015) - Schmiele, Martin; Knittel, Charlotte; Unruh, Tobias; Busch, Sebastian; Morhenn, Humphrey; Boesecke, Peter; Funari, Sérgio S.; Schweins, Ralf; Lindner, Peter; Westermann, Martin; Steiniger, Frank
<x xml:space="preserve">Abstract</x> DNA-complexes with platelet-like, cationically modified lipid nanoparticles (cLNPs) are studied with regard to the formation of nanocomposite structures with a sandwich-like arrangement of the DNA and platelets.